2013
DOI: 10.1186/1755-8794-6-47
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D related genes in lung development and asthma pathogenesis

Abstract: BackgroundPoor maternal vitamin D intake is a risk factor for subsequent childhood asthma, suggesting that in utero changes related to vitamin D responsive genes might play a crucial role in later disease susceptibility. We hypothesized that vitamin D pathway genes are developmentally active in the fetal lung and that these developmental genes would be associated with asthma susceptibility and regulation in asthma.MethodsVitamin D pathway genes were derived from PubMed and Gene Ontology surveys. Principal comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 52 publications
3
62
0
Order By: Relevance
“…These findings support previously published epidemiologic data that have linked vitamin D-responsive genes to early lung development and asthma phenotypes (35,36). Vitamin D3 at the cellular level functions as a growth factor for alveolar type II cells, which are important in promoting alveolarization during lung growth and development (37).…”
Section: Discussionsupporting
confidence: 80%
“…These findings support previously published epidemiologic data that have linked vitamin D-responsive genes to early lung development and asthma phenotypes (35,36). Vitamin D3 at the cellular level functions as a growth factor for alveolar type II cells, which are important in promoting alveolarization during lung growth and development (37).…”
Section: Discussionsupporting
confidence: 80%
“…Evidence suggests that vitamin D may stimulate regulatory T cell development and T cell function to suppress inappropriate Th1 and Th2 responses to environmental exposure (i.e., allergens, infection load), leading to a more balanced immune response inhibiting autoimmune diseases (with Th1 dominance) and allergic diseases (Th2 dominance) (55). Vitamin D could therefore be involved in lung diseases of early childhood through immunomodulatory effects.Although controversial, several epidemiological studies have described an association between maternal vitamin D deficiency and the development of early childhood respiratory infections, wheezing, and asthma later in life (15,16,47,91).Human lung development begins in the fifth fetal week and continues throughout the first few years of life. It includes five phases: the embryonic, pseudoglandular, canalicular, saccular, and alveolar phase ( Fig.…”
mentioning
confidence: 99%
“…Although controversial, several epidemiological studies have described an association between maternal vitamin D deficiency and the development of early childhood respiratory infections, wheezing, and asthma later in life (15,16,47,91).…”
mentioning
confidence: 99%
“…First, vitamin D deficiency is recognized worldwide, and there are data indicating that levels have decreased over time, coincident with the rise in autoimmunity and asthma (11). Next, vitamin D has effects on the developing lung (12), and we have shown that vitamin D-related developmental genes are up-regulated in early lung development and that these same genes are linked to asthma (13). Third, vitamin D has effects on a variety of immune processes and cells that are critical to normal immune functioning (14).…”
mentioning
confidence: 87%